Low-temperature quartz wafer bonding using hyperbranched polyurethane oligomers - Zhao, J.; Jin, F.; Zhao, J.; Liu, Shaomin (Springer, 2014)
In this paper, we introduce a new bonding technology for the assembly of micro- structured glass substrates for miniaturized chemical analysis. The protocol features a facile polymer chemistry method processing at lower temperatures (<100 °C). The method consisted of a proper cleaning of the two glass surfaces, followed by hydroxylization, aminosilylation and hyperbranched polyurethane oligomers (HPU) bridging on quartz wafer surfaces as the interlayer. Strong bonding with a shear force 4.5 MPa has been achieved. The present procedure avoids the possible micro-channel blockage and contamination by using conventional adhesives. Moreover, the microfluidic chips bonded by the above procedures are highly transparent therefore allowing for biochemical compositions to be easily characterized by UV–vis or IR spectroscopy.